An optimized off-grid hybrid system for power generation in rural areas - Jamil Al Asfar; Ahmad Sakhrieh; Nour Abu Shuaib (Institute of Advanced Engineering and Science, 2022)
Stand-alone hybrid power generation system for a cow farm in Jordan is economically and technically optimized to meet the daily electrical load of the farm. A combination of photovoltaics, biogas generators, diesel generators, wind turbines, and batteries are used to determine the best scenario for the farm's power generation. In accordance with the price and technical data of the components, the systems were first studied technically and economically, and then simulated using hybrid optimization model for multiple energy resources (HOMER) software to identify the best configuration. Several options were analyzed to determine the best configuration. The optimized hybrid system includes photovoltaics, a biogas generator, batteries, and a diesel generator. The optimum configuration had a levelized cost of energy of 0.06 per kWh and a net present cost of 2,100,000. The renewable fraction of the total system electrical yearly production was 94%. Furthermore, the results showed that the optimized hybrid system could reduce the emitted gasses by about 92%.